Entangled photons and quantum communication - Yuan, Zhen-Sheng; Bao, Xiao-Hui; Lu, Chao-Yang; Zhang, Jun; Peng, Cheng-Zhi; Pan, Jian-Wei (Physics reports, 2010)
This article reviews the progress of quantum communication that utilizes photonic entanglement. We start with a survey of various methods for generating entangled photons, followed by an introduction of the theoretical principles and the experimental implementations of quantum key distribution. We then move on to a discussion of more involved quantum communication protocols including quantum dense coding, teleportation and quantum communication complexity. After that, we review the progress in free-space quantum communication, decoherence-free subspace, and quantum repeater protocols which are essential ingredients for long-distance quantum communication. Practical realizations of quantum repeaters, which require an interface between photons and quantum memories, are discussed briefly. Finally, we draw concluding remarks considering the technical challenges, and put forward an outlook on further developments of this field.